2020
DOI: 10.1080/13504622.2020.1750568
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary primary school curriculum units for sustainable development

Abstract: Education for sustainable development (ESD) provides crucial opportunities for young people to be involved in complex sustainability issues. This study contributes to existing knowledge about primary school teachers' approaches to ESD across a range of subjects.Norwegian schools can join the Sustainable Backpack programme (SBP), which supports teachers to develop projects that promote a holistic understanding of sustainable development across school subjects. The present study set out to examines teachers' int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 35 publications
(43 reference statements)
0
12
2
Order By: Relevance
“…In this study, Chinese immigrant teachers also perceive these are their teaching outcomes. Although previous studies (Eli et al, 2020;Summers et al, 2005) suggested that language teachers are less motivated in bringing in sustainable development topics in their lessons, this study reflected that Chinese immigrant teachers perceive sustainable development topics such as gender equality and responsible consumption as an opportunity to achieve higher-order thinking skills. Such perception influences them positively that they are more willing to devote more time to prepare the relevant materials, thereby enhancing the overall quality of their lessons (Basilaia & Kvavadze, 2020;Kwee, 2021a Previous studies (Cho, 2010;Roy, 2016;Santoro, 2007) suggested that immigrant teachers generally have to spend more time on lesson preparation.…”
Section: Enhancing Students' Higher-order Thinkingcontrasting
confidence: 59%
See 1 more Smart Citation
“…In this study, Chinese immigrant teachers also perceive these are their teaching outcomes. Although previous studies (Eli et al, 2020;Summers et al, 2005) suggested that language teachers are less motivated in bringing in sustainable development topics in their lessons, this study reflected that Chinese immigrant teachers perceive sustainable development topics such as gender equality and responsible consumption as an opportunity to achieve higher-order thinking skills. Such perception influences them positively that they are more willing to devote more time to prepare the relevant materials, thereby enhancing the overall quality of their lessons (Basilaia & Kvavadze, 2020;Kwee, 2021a Previous studies (Cho, 2010;Roy, 2016;Santoro, 2007) suggested that immigrant teachers generally have to spend more time on lesson preparation.…”
Section: Enhancing Students' Higher-order Thinkingcontrasting
confidence: 59%
“…On the other hand, it gave a holistic view on the interrelationship between self-efficacy and teaching performance attainment, thereby allowing insights on effective pedagogies Chinese immigrant teachers adopt to attain their teaching goals alongside boosting their motivation (Brown & Lent, 2019;Lent et al, 1994). For example, this study challenged the previous studies (Eli et al, 2020;Summers et al, 2005) that there is low motivation of language teachers incorporating topics related to sustainable development; instead, this study reflected that such topics allow Chinese immigrant teachers to enhance students' higher-order thinking, leading to their high selfefficacy and positive teaching outcome expectations. Such information provides insight for educational institutions and universities to provide or polish their professional development courses and teacher training for both HL teachers and immigrant teachers.…”
Section: Discussionmentioning
confidence: 81%
“…It is worth mentioning to state that the curriculum of schools develops public opinion, ideologies, and patriotism of the nation (Byrne & Prendergast, 2020). In Pakistan and several other developing nations, lack of infrastructure and funding issues (Gleeson et al, 2020), curriculum design and reforms are major concerns to change the education system (Eli et al, 2020). Thus, the developed world imposes sanctions and strict conditions on developing countries to receive funding (Zhao, 2020) and influence curriculum development as well (Jang, 2020).…”
Section: Curriculum Development At the School Levelmentioning
confidence: 99%
“…Such skills were deemed essential in improving the proficiencies of language learning (Ellis, 2000;Hyland, 2007). Moreover, by integrating global issues in such a creative ESL classroom, students were able to further develop higher-order thinking skills such as critical thinking and system thinking, which is considered as essential in this era of education (Eli et al, 2020). Some participants expressed their thoughts about multiple online field trips to local history museums in their community during classes (Kamen and Leri, 2019).…”
Section: Expanding the Knowledge To Other Subjectsmentioning
confidence: 99%